Distribusi, Retensi, dan Penetrasi Bahan Pengawet Ekstrak Daun Tuba (Derris elliptica Benth) pada Kayu Kemiri dan Kayu Agathis (Distribution, Retention, and Penetration of Tuba Leaves Extract (Derris elliptica Benth) on Aleurites moluccana and Agathis Wood) - Syahidah Syahidah; Andi D Yunianti (Masyarakat Peneliti Kayu Indonesia, 2019)
Wood preservation is carried out to increase the service life of wood with low natural durability. Factors such as wood structure, preservatives, and methods of preservation influence the preservation processes. The aim of this study was to evaluate retention, penetration, and distribution of tuba (Derris elliptica) leaves extract into the candlenut wood (Aleurites molluccana) and agathis (Agathis sp.) wood structures. The wood samples were treated with hot and cold soaking. The duration of hot soaking were 3, 5, and 7 hours, while for cold soaking were 3, 5, and 7 days. The result showed that the highest retention of extract was achieved by cold soaking for 7 days at 9.4 kg m-3, and the lowest retention was achieved by hot soaking for 3 hours at 1.9 kg m‑3. The highest penetration occured by cold soaking for 7 days at 8.08 mm and the lowest was that with hot soaking for 3 hours at 2.81 mm. However, the distribution of the extract in the agathis wood structures could not be detected by stereo microscope. In the the case of the candlenut wood, the extract was distributed in the parenchyma cell.